Carcass And Meat Characteristics Of Quail Reared Under Intensive System In Kashmir - Malik, A.H.; Wani, Sarfaraz A; Pal, M. A.; Salahuddin, Mir; Sofi, Asif H; Banday, M. T.; Shahnaz, Syed (Journal of Meat Science, 2012)
A study was conducted to assess the carcass and meat characteristics of Japanese quail reared under intensive system in temperate climatic conditions of Kashmir valley. After recording the average live weights (188.98±0.36 gms), birds were slaughtered by halal method. The mean±S.E bled-out, defeathered and dressed weights (gms) were recorded as 180.7±0.35, 171.2±0.35 and 139.05±0.33, respectively. The dressing percentage was recorded as 73.87±0.20. The percent yield of inedible offals; viz: blood, feathers, head and shanks was 4.39±0.08, 5.06±0.10, 4.99±0.07 and 2.30±0.05, respectively on live weight basis. The total giblets percent on live and dressed weight basis were 4.99±0.07 and 2.30±0.05, respectively. The moisture, crude protein, ether extract and ash were found as 74.14±0.63 (%), 20.22±0.79 (%), 4.11±0.52 (%) and 2.45±0.18 (%). Although quail meat is less common in Kashmir and considered a delicacy but the carcass and meat quality revealed its potential as a supplementary source of meat.